2016
DOI: 10.3349/ymj.2016.57.5.1236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-Implantation of a Capsular Tension Ring on Clinical Outcomes after Cataract Surgery with Monofocal Intraocular Lens Implantation

Abstract: PurposeThe objective was to evaluate the effect of co-implantation of a preloaded capsular tension ring (CTR) and aberration-free monofocal intraocular lens (IOL) on clinical outcomes and visual quality after cataract surgery.Materials and MethodsPatients who underwent cataract surgery were randomized into two groups that were implanted with a CTR and IOL (group 1, 26 eyes) or an IOL only (group 2, 26 eyes). At 1 and 3 months after surgery, visual acuity, refractive errors, refractive prediction errors, ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
1
14
1
1
Order By: Relevance
“…CTR can effectively balance the tension of zonular fibers, uniformly distribute the tension of the capsular bag, maintain the shape of the capsular bag, reduce loss of the vitreous body, and increase the attachment between posterior capsule and IOL surface. Therefore, CTR implantation can increase IOL stability after cataract extraction involving IOL implantation and reduce the occurrence of posterior capsule opacification and IOL dislocation [7,[23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the benefits of CTR implantation in patients with weakened zonular fibers but no lens dislocation is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTR can effectively balance the tension of zonular fibers, uniformly distribute the tension of the capsular bag, maintain the shape of the capsular bag, reduce loss of the vitreous body, and increase the attachment between posterior capsule and IOL surface. Therefore, CTR implantation can increase IOL stability after cataract extraction involving IOL implantation and reduce the occurrence of posterior capsule opacification and IOL dislocation [7,[23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the benefits of CTR implantation in patients with weakened zonular fibers but no lens dislocation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The CTR maintains the shape of the capsular bag, balances the tension in zonular fibers, and decreases the risk of capsular shrinkage and IOL decentration or dislocation [23][24][25][26][27][28][29][30]. While CTR has been used to treat focal zonular rupture or diffuse zonulopathy by stretching out the capsular bag or facilitating scleral suture fixation [7,[23][24][25][26][27][28][29][30][31][32][33][34][35], it is unclear whether the capsular bag and IOL can remain stable after CTR implantation during cataract surgery in patients with strong myopia [7,23,35]. In addition to these uncertainties, the effects of CTR on cataract surgery in patients with an abnormal zonule after PPV are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CTR can effectively balance the tension of zonular bers, uniformly distribute the tension of the capsular bag, maintain the shape of the capsular bag, reduce loss of the vitreous body, and increase attachment between posterior capsule and IOL surface. These effects of CTR increase IOL stability after cataract extraction involving IOL implantation and reduce the occurrence of posterior capsule opaci cation and IOL dislocation [7,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Whether and how CTR implantation can also bene t patients with weakened zonular bers but no lens dislocation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The CTR maintains the shape of the capsular bag, balances the tension in zonular bers, and decreases the risk of capsular shrinkage and IOL decentration or dislocation [22][23][24][25][26][27][28][29]. While a CTR has been used for focal zonular rupture or diffuse zonulopathy either to stretch out a capsular bag or to facilitate scleral suture xation [7,[22][23][24][25][26][27][28][29][30][31][32][33][34], other studies suggested that whether the capsular bag and IOL can remain stable after CTR implantation during cataract surgery in patients with strong myopia are controversial [7,22,34]. In addition to these uncertainties, the effects of CTR on cataract surgery in patients with an abnormal zonule after PPV are unclear.…”
mentioning
confidence: 99%
“…Однако действующая классификация подвывиха хрусталика не оперирует достоверными количественными данными о протяженности повреждения связочного аппарата и не позволяет адекватно планировать хирургическое вмешательство. Развитие технологий в катарактальной хирургии дало возможность использования интраоперационных способов стабилизации капсульного мешка хрусталика путем имплантации устройств различной модификации, стабилизирующих капсулу [6,7].…”
unclassified